Prosedur Pemeriksaan Dacryocystografi Pada Kasus Dacryosistitis Kronis Di Instalasi Radiologi RSUP. Dr.Wahidin Sudirohusodo Makassar - Rini Hatma Rusli; Bambang Ariyanto; Akhmadi Akhmadi; Miranda Waas; Amelia Niwele (Jurnal Sains dan Kesehatan, 2022)
Dacryocystography examination is the examination of the radiologist to show the nasolacrimal duct by using a positive contrast medium. The purpose of this examination is to describe the system of tear duct blockage and the level of blockage. This research method is descriptive with aproachcase study conducted in RSUP. Dr. WahidinSudirohusodo Makassar on Juni 2019. The inspection technique is done by using the projection Antero Posterior (AP), which contrast material is inserted throught the tear duct in the lacrimal punctum which empties into the concha nasalis inferior. From the result of the examination has been done, it can be concluded that the contrast as much as 1 cc inserted throught the superior lacrimal punctum, contrast restrained and spilled out. Contrast as much as 1 cc inserted throught the inferior lacrimal punctum, the contrast seems to fill out the inferior palpebra area. From the research, lacrimal duct obstruction impression superior and inferior.